The Phenolic, Flavonoid, and Anthocyanin Content From Methanol Extract of Senggani Fruit and Its Antioxidant Activity - Purwaningsih, Indah; Fathiah, Fathiah; Amaliyah, Nurul; Kuswiyanto, Kuswiyanto (Indonesian Journal of Chemical Research, 2023)
Senggani fruit is an edible fruit that tastes sweet, has an attractive color, blue or reddish purple, and is thought to contain anthocyanin. The senggani fruit can be used as a source of natural dyes and is known to have active components as a source of antioxidants. This study aimed to measure the phenolic, flavonoid, and anthocyanin content and the antioxidant activity of the methanol extract of senggani fruit. Senggani fruits were extracted by maceration using methanol. The phytochemical screening test was performed. The phenolic, flavonoid, and anthocyanin content was measured using the Folin-Ciocalteu, AlCl3, and pH differential, respectively. The antioxidant activity test was carried out using the DPPH method. The phytochemical screening test showed the methanol extract of senggani fruit contained phenols, flavonoids, alkaloids, saponins, and tannins. In this study, the total phenol content was 154.880 mg GAE/g, the total flavonoid content was 6.827 mg QE/g, and the anthocyanin level was 7.516 mg/100 g. The antioxidant activity using the DPPH method showed that the methanol extract of senggani fruit had moderate antioxidant activity, with an IC50 value of 99.79 ppm.